2015
DOI: 10.1007/s00404-015-3724-z
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative outcomes and prospective patient reported outcome measures for transvaginal mesh surgery

Abstract: Our data revealed a very low intraoperative complication rate with a mesh exposure rate of 4 %. The prospective study showed a statistically significant improvement in vaginal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
3
9
1
Order By: Relevance
“…There is little data concerning defecation situation after POP surgery with meshes. Some studies reported less constipation than before [17]. Unlike them, we found a worsening of this symptom in our patients, which was statistically significant, although there were some of them in whom it improved.…”
Section: Commentcontrasting
confidence: 73%
See 2 more Smart Citations
“…There is little data concerning defecation situation after POP surgery with meshes. Some studies reported less constipation than before [17]. Unlike them, we found a worsening of this symptom in our patients, which was statistically significant, although there were some of them in whom it improved.…”
Section: Commentcontrasting
confidence: 73%
“…In October 2008, the FDA responded to the emerging complications related to the meshes, followed by an updated safety communication in July 2011. However, there are currently scarce data with regard to long-term results and complications [16,17]. The majority of studies published are retrospective [13,14,18], and those which are prospective have a short or medium follow-up.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no consistent method of presenting the assigned CTS codes. Some reported summaries or general descriptions of assigned codes [3,16,21,25], whereas others specified both the unique CTS codes and the number of patients assigned codes [2,4,5,14,15,[17][18][19][20][22][23][24]. One publication assigned codes to the cohort upon initial presentation and again following prosthesis/graft removal [5].…”
Section: Resultsmentioning
confidence: 99%
“…Mesh exposure and invasion are the most common complications after TVM placement. According to previous literature report, the mesh exposure rate ranges from 1.4% to 36% 18,19,21,22 , while in the Cochrane review 1 , the mesh exposure rate is 12%, and 8% patients require further surgical treatment. In our study, only 2 (2.2%) patients had asymptomatic recurrence during postoperative follow-up ,but no further treatment was selected owing to little impact on quality of life.…”
Section: Discussionmentioning
confidence: 98%